Japanese-speaking Politeness Used in Hotaru no Hoshi Movie Through The Study of Sociolinguistic - Istiqomah Dewi Agustina (Chi'e: Journal of Japanese Learning and Teaching, 2018)
The purpose of this research is to found out the Japanese-speaking politeness that used by Japanese people in social interaction. This research also intent on knowing about language in use, especially the structure of honorifics in use to expressing Japanese-speaking politeness. This research use descriptive-qualitative approach. The data consist of conversation dialogues, based on social rules of politeness when Japanese people interact each other. This data originated from Japanese movie â€œHotaru no Hoshiâ€ that direct by Hiroshi Sugawara. Data was collected by observing use of language in conversations while make a note without involve those conversations. Data was analyzed by Â â€œpadan ekstralingualâ€ method and study of sociolinguistics. The result of data analysis explain that Japanese-speaking politeness was expressed by: greeting the addressee with appropriate name (with titles or professional ranks); using polite language (teineigo) when speaking in a formal setting; using sentence final particle â€œneâ€ (isnâ€™t it?) to show empathy toward addressee; and use of polite language to manipulate psychological attitude toward the other participants.